The role of health workers in the conditions of global pandemics – beliefs of students - Milošević Georgiev, Andrijana; Krajnović, Dušanka; Hadžibegović, Nela; Šesto, Sofija (Archives of Pharmacy, 2022)
Throughout history, people have been affected by numerous pandemics, whether caused by human factors or natural disasters and calamities. In the conditions of epidemics, health workers also become vulnerable, and as a priority they put the needs of their patients above their own. The aim of the research was to examine beliefs of students regarding the obligations of health workers in the conditions of global pandemics, on a sample of 268 students from the Faculty of Pharmacy, University of Belgrade were interviewed using a purpose-built questionnaire. The mean age was 21.41±2.11. Dominated by females (87.3%), from the fifth year of study (35%) and with a completed secondary vocational school (52.2%). The majority of respondents (91%) believe that by choosing a profession they consciously accept the possibility of being exposed to a high risk of infectious diseases. But, 67.5% of students stated that they were not fully awared of all the risks that characterize the profession of health worker and the risk to their health while dealing with sick patients, as well as the way of their own protection. More than half of respondents (56%) would refuse to provide medical care to a high-risk patients if they did not have adequate protection. The obtained results indicate that there is a certain level of concern for the safety of health workers in the conditions of a global pandemic.